Total Phenolics, Flavonoids, and ɑ-Glucosidase Inhibitory Activity of Red Betel (Piper crocatum) Extract in Various Solvents - Abdullah, Wais; Seno, Djarot Sasongko Hami; Safithri, Mega (Indonesian Journal of Applied Research (IJAR), 2024)
Alpha-glucosidase enzyme activity needs to be inhibited to avoid increasing blood sugar levels in diabetics. Red betel leaf extract is reported to have active compounds such as phenolics and flavonoids that have alpha-glucosidase enzyme inhibition activity. Previous research showed that 70% betel leaf extract has an ɑ-glucosidase enzyme inhibition activity of 69.84%, but it is not yet known how the effect of extracts with different levels of polarity on the inhibition activity of alpha-glucosidase enzyme. This study aimed to determine extracts that have optimal levels of phenolic and flavonoid content and the highest suppression of α-glucosidase activity. The multistage maceration method was used to extract red betel leaf simplicia using solvents with different levels of polarity (n-hexane, ethyl acetate, methanol). Tests were conducted on overall phenolic concentration, flavonoids, and ɑ-glucosidase inhibition ability. Data were analyzed using one-way ANOVA test with Tukey's further test (p<0.05). The results of the assessment of phenolic concentration, flavonoids, and α-glucosidase inhibitory activity as a whole showed statistically significant differences (p<0.05) in all extracts with the highest total phenolic and flavonoid content found in the n-hexane extract of 25.68 ± 0.29 mg GAE/g and 65.84 ± 0.96 mg QE/g respectively. Meanwhile, methanol extract of red betel leaf became the best extract in this study with the greatest inhibition among all extracts with a percent α-glucosidase inhibition value of 43.87 ± 1.83%.